(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Muslichahah S, Azrianingsih R, Indriyani S, Arumingtyas EL. 2022. Papeja, herbal potions during breastfeeding in Madura (Indonesia): The use, perceived effectiveness, and documentation of the plants used. Biodiversitas 23: 5139-5148. The World Health Organization recommends breastfeeding as the normal infant feeding method. However, many women often face challenges in breastfeeding their infants. One of the challenges may be a real or perceived insufficient milk supply. Poor breast milk production is the common cause of breastfeeding failure in preterm babies. In Indonesia, Madurese women use Papeja (herbal medicines) as a herbal potion to enhance breast milk production. Hence, this study aims to identify the pattern of use, perceived effectiveness, and galactagogues plant component of Papeja taken by mothers during breastfeeding in the Sub-districts of Guluk-Guluk and Pasongsongan, Sumenep District. The data were collected through interviews using a semi-structured questionnaire. Sixty women who had agreed to be interviewed, 18 years or older, breastfeeding or breastfeeding in the past 24 months, and two traditional midwifery in the study area were interviewed. We used simple descriptive statistics to summarize the data on demographic, respondent attitudes, and galactagogues plants. Most participants (n = 48) perceived that the herbal galactagogues effectively promoted breastfeeding adequacy. We identified 46 plants from 27 families to have been used in Papeja. Some of the plants used by the mothers have been recorded as having benefits for enhancing milk supply, some have not had that information, but most have not yet been chemically tested. Thus, it is important to validate the plants scientifically for possible galactagogues properties, which can be harnessed for future use. Since we recorded those plants as ethnomedicinal and therapeutic plants, phytochemical and pharmacological investigations are recommended because this could lead to developing new medicine to address poor milk production among mothers.